Ultraviolet Emission From Resonant Tunnelling Metal–Insulator– Semiconductor Light Emitting Tunnel Diodes - Chen-Sheng Lin; Kate Cavanagh; Hei-Chit L. Tsui; Andrei Mihai; Bin Zou; Duncan W.E. Allsopp; Michelle A. Moram (IEEE Photonics Journal)
Strong room-temperature electroluminescence at 365 nm has been demonstrated from simple Au/AlN/ n-GaN metal–insulator–semiconductor (MIS) light emitting diodes, which do not contain p -doped material. Current-voltage and electroluminescence data indicate that an AlN insulating layer thickness of 10 nm results in optimized diode behavior and maximum ultraviolet emission: At lower thicknesses carriers tunnel easily through the barrier, whereas at greater thicknesses the forward resistivity is excessively high. A decrease in emission intensity was observed at high injection currents due to Fowler–Nordheim tunnelling. However the device efficiency was found to improve by a factor of 10 when the AlN layer and the metal contact layer were deposited without breaking vacuum, thereby preventing any contamination or oxidation of the AlN surface. Additionally, this MIS device showed clear resonant tunnelling characteristics which are correlated with the enhanced light emission intensity.